The green development effect of science and technology financial policy in China - Zou, Xuxin; Min, Jiadi; Meng, Shuang (Frontiers in Environmental Science, 2024)
Green development, as a key link in the philosophy of new development, is the only way to achieve sustainable development. However, how science and technology (S&T) finance affects green development remains unclear. Based on panel data of 284 cities in China from 2007 to 2020, the multi-time-point difference-in-differences (DID) model and the mediation model were utilized to analyze the influencing mechanisms and paths of the S&T financial pilot policy on green development. The results show that S&T financial policy can significantly promote green development, for which green innovation (GI) capability, industrial structure advancement (ISA), and industrial structure rationalization (ISR) are important paths. Moreover, the effects of S&T financial policy on green development are heterogeneous: the policy exerts a stronger effect on the central region than on the eastern and western regions, a stronger effect on large cities than on small- and medium-sized cities, and a stronger effect on key cities than on general cities. Therefore, relevant governmental departments should continually optimize S&T financial policy; pay more attention to cities in the western region, small- and medium-sized cities, and general cities; actively foster GI capability; facilitate industrial structure transformation and upgrading; and vigorously support cross-regional exchange and cooperation to jointly realize green development. This study sheds new light on how the S&T finance related policy reform promotes sustainable growth and socio-economic welfare in developing countries.